Inovasi Pembelajaran PAI melalui Penerapan Metode Talking Stick pada Materi Gibah dan Tabayun di SMP 1 Kudus - Farandika Nanda Pratama; Sanusi Sanusi; Fitra Irpandi (ANWARUL, 2025)
This study is motivated by the need for innovation in PAI learning to increase student activeness and understanding, especially on the material “Avoiding Gibah and Carrying out Tabayun.” The lecture method which is still dominant often causes boredom, so a more interactive approach is needed. This study aims to analyze the content of grade 7 PAI learning materials, examine the concept of the talking stick method, and evaluate its application in the material using a qualitative approach through a case study method conducted in class 7H SMP 1 Kudus. Data were collected through observation, interviews with PAI teachers and students, and documentation of teaching materials. The results showed that the teaching materials used were in accordance with the curriculum standards, although the learning outcomes were not explicitly stated so that teachers needed to adjust them with additional references. The application of the talking stick method proved effective in increasing students' active participation, critical thinking skills, and understanding of the concepts of gibah and tabayun. However, there were obstacles in time management and equal distribution of speaking opportunities. In addition, this research contributes to the development of PAI learning methods that are more innovative and relevant to students' learning styles and needs. With the modification of this method, it can be an effective alternative in shaping students' characters to be wiser in communicating and applying the principle of tabayun in daily life.